Islamic Law's Responsibility for Environmental Damage: The Perspective of Islamic Legal Philosophy - Khairuddin Hasibuan (ISNU Nine-Star Multidisciplinary Journal, 2024)
Environmental damage is one of the global problems that has a broad impact on human life. From an Islamic perspective, the environment has a sacred value that must be maintained, as stated in the Qur'an and Hadith. Responsibility for environmental sustainability is not only moral but also has legal implications. This study aims to analyze Islamic legal responsibility for environmental damage based on the perspective of Islamic legal philosophy, which emphasizes the principles of justice, benefit, and balance. This study uses a qualitative method with a descriptive analysis approach to explore the concept of Islamic legal responsibility in the context of environmental damage. Data were collected through a literature study of Islamic legal sources, including the Qur'an, Hadith, and the opinions of classical and contemporary scholars. The results of the study show that Islam provides a strong normative foundation in environmental protection, with basic principles such as the prohibition of destruction (fasad) and the obligation to maintain balance (mizan). Sanctions in Islamic law, both in the form of hudud, ta'zir, and diyat, can be applied in the context of environmental crimes. In conclusion, Islamic law has a comprehensive mechanism to overcome environmental damage with a holistic and just approach.